Relationship of matrix metalloproteinase-3 -11715A/6A polymorphism (rs35068180) and dilated cardiomyopathy - S. Yu. Nikulina; O. O. Kuznecova; A. A. Chernova; V. N. Maksimov (Российский кардиологический журнал, 2020)
Aim. To study the relationship of matrix metalloproteinase-3 (MMP3) genetic polymorphism and dilated ischemic cardiomyopathy (DCM), as well as idiopathic cardiomyopathy (ICM) of unknown etiology.Material and methods. A total of 221 patients with DCM and ICM were examined (mean age, 55,30±9,69 years). The group of ischemic DCM consisted of 111 people (99 men (89,2%) and 12 women (10,8%)). The mean age of DCM subjects was 51,73±9,74 years (male subgroup, 51,00±8,96 years; female subgroup, 57,75±3,71 years). The ICM group consisted of 110 people (100 men (91,5%) and 10 women (8.5%)). The mean age of ICM subjects was 58,68±8.38 years (male subgroup, 58,29±8.,6 years; female subgroup, 62,90±6,29 years). The control group of subjects (n=121) consisted of healthy people without cardiovascular diseases (mean age, 53,6±4,8 years). All patients of the experimental group underwent routine diagnostic tests, as well as coronary angiography. In case of suspected myocarditis, cardiac magnetic resonance imaging was performed. All patients underwent polymerase chain reaction to determine the MMP3-11715A/6A polymorphism (rs35068180).Results. In patients with cardiomyopathy, regardless of the disease origin, significant differences were verified in comparison with the control group. Allele 6A (65,8% vs 59,3%, p=0,044) and genotype 6A/6A (42,1% vs 32,6%, p=0,099) were found significantly more frequently in patients with cardiomyopathy than in the control group. In addition, despite various etiological factors, the pathogenetic involvement of MMP3 is likely to have a general direction.Conclusion. In all patients with cardiomyopathy, the prevalence of MMP3 gene A allele was shown. Due to decrease in the transcription activity in homozygous 6A allele, the stromelysin level in arterial walls also decreases. This promotes the activation of procollagenase-1, the deposition of extracellular matrix and cardiac remodeling